2023
DOI: 10.1371/journal.pone.0290350
|View full text |Cite
|
Sign up to set email alerts
|

What socio-demographic factors support disposable vs. sustainable menstrual choices? Evidence from India’s National Family Health Survey-5

Karan Babbar,
Supriya Garikipati

Abstract: For over a decade, improving menstrual hygiene among poor girls and women in low-and-middle-income-countries has been a prominent global goal. Towards this, governments in the Global South have worked to promote the uptake of disposable sanitary pads. Despite this, we continue to see a high prevalence of period poverty mainly because disposable pads require monthly purchasing that may be burdensome for many women. Not only are pads financially unsustainable but also represent a heavy environmental burden which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…According to a study by Babbar et al, several sociodemographic factors influence the use of modern menstrual products, such as menstrual cups and tampons. These factors include the level of education, place of residence (urban or rural), family income, socioeconomic status, freedom of movement, access to basic handwashing and sanitation facilities, access to toilets, social taboos against vaginal insertion, exposure to media, and use of mobile phones [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Babbar et al, several sociodemographic factors influence the use of modern menstrual products, such as menstrual cups and tampons. These factors include the level of education, place of residence (urban or rural), family income, socioeconomic status, freedom of movement, access to basic handwashing and sanitation facilities, access to toilets, social taboos against vaginal insertion, exposure to media, and use of mobile phones [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since psychological hesitation and apprehension about the initial use of MCs are key among Japanese consumers, as found in our study, which is also in line with a previous study (Itaya et al, 2022), KOLs can play a critical role in demystifying MCs and addressing common concerns through trusted endorsements. In line with this, recent studies have shown that education and mass media exposure significantly increase the likelihood of adopting menstrual cups (Babbar and Garikipati, 2023;Balkan and Koyucu, 2024). Furthermore, educating about menstrual cups aligns with Sustainable Development Goal (SDG) 5 by reducing the stigma around menstruation and fostering a more inclusive and equal society.…”
Section: Implications For Promoting MC (Rq4)mentioning
confidence: 80%
“…According to previous research, a woman uses an average of 10,000 sanitary napkins and 15,000 tampons on average during their lifetime (Bharadwaj and Patkar, 2004;Garg et al, 2011). Moreover, advertised menstrual products such as tampons or sanitary pads are estimated to take approximately 500-800 years to decompose, constituting a staggering burden on the environment (Sathishkumar et al, 2019;Peter and Abhitha, 2021;Babbar and Garikipati, 2023;Khorsand et al, 2023). In addition to ecological predicaments, each sanitary napkin emits 2-3.7 g of non-biodegradable plastic, and given the prevalence of plastic in these products, their complete biodegradation remains elusive (Ando et al, 2023;Kumari and Muneshwar, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation